2011
DOI: 10.2119/molmed.2010.00214
|View full text |Cite
|
Sign up to set email alerts
|

S1P Is Associated with Protection in Human and Experimental Cerebral Malaria

Abstract: Cerebral malaria (CM) is associated with excessive inflammatory responses and endothelial activation. Sphingosine 1-phosphate (S1P) is a signaling sphingolipid implicated in regulating vascular integrity, inflammation and T-cell migration. We hypothesized that altered S1P signaling during malaria contributes to endothelial activation and inflammation, and show that plasma S1P levels were decreased in Ugandan children with CM compared with children with uncomplicated malaria. Using the Plasmodium berghei ANKA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 68 publications
6
75
1
Order By: Relevance
“…In addition, our observations of endothelial activation and dysfunction following P. berghei ANKA infection are in agreement with accumulating evidence that increased levels of sICAM-1 and Ang-2, and decreased levels of Ang-1 are associated with both adverse clinical outcomes in human malaria infections and progression of ECM in mice (5,34,(45)(46)(47)(48)53). Of note, in the same cohort of Ugandan children with CM we studied with increased C5a levels, we also observed significantly increased levels of sICAM-1 and Ang-2 compared to those in children with uncomplicated malaria (34).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, our observations of endothelial activation and dysfunction following P. berghei ANKA infection are in agreement with accumulating evidence that increased levels of sICAM-1 and Ang-2, and decreased levels of Ang-1 are associated with both adverse clinical outcomes in human malaria infections and progression of ECM in mice (5,34,(45)(46)(47)(48)53). Of note, in the same cohort of Ugandan children with CM we studied with increased C5a levels, we also observed significantly increased levels of sICAM-1 and Ang-2 compared to those in children with uncomplicated malaria (34).…”
Section: Discussionsupporting
confidence: 91%
“…Similar observations have been reported in ECM after P. berghei ANKA challenge (47,48). Consistent with these studies, we observed that P. berghei ANKA infection was associated with decreased levels of Ang-1 and increased levels of sICAM-1 in all three groups (Fig.…”
Section: Deletion Of C5ar But Not C5l2 Improves Survival In a Mouse Msupporting
confidence: 92%
“…Four studies determined the Ang-1 and/or the Ang-2 level in humans after start of anti-malarial treatment [29, 34, 36, 37]. Three studies investigated the effect of adjuvant therapy next to standard treatment on survival and on Ang-1 and/or Ang-2 levels in mice [3840], two in humans [41, 42] and one in both humans and mice [26] during Plasmodium species infection (see Additional file 6). One study used a mouse model with one deleted Ang-1 allele [26] (see Additional file 6).…”
Section: Resultsmentioning
confidence: 99%
“…Areas that require further study (“?”) include the role of PARs in CM and the extent to which ARs on ECs and DCs are critical in the DF-induced protective response against CM. Paradoxically, S1P receptors are implicated in the coagulation-inflammation cycle, 15 yet availability of S1P is important for protection against CM; 31 , therefore, the interactions between ARs, PARs, and S1P receptors, both in pathogenesis and in the context of DF treatment, should be investigated.…”
Section: Figurementioning
confidence: 99%